Documentation Bulletin No.4 - Planning Commission (Planning Commission, 1969)
Soil conservation is the only land improvement measure applicable to the vast un-irrigated areas particularly in the prior parts of India. The techniques and methods of conservation have been devised in the country comparatively recently and are in node of further development to suit local and regional conditions. While a national programme for soil conservation was conceived and initiated in the First Plan, it was only towards the later part of the Second Plan that the programme get sufficiently organised. In the Third Five-Year Plan, it has been taken up on a larger scale with a target more than five times that in the Second Plan. There has also been a very large increase in the programme for dry farming.
Programme Evaluation Organisation Planning Commission Government of India
Programme Evaluation Organisation Planning Commission Government of India